GENERAL CATALOGUE OF VARIABLE STARS - Samus, N. N.; Kazarovets, E. V.; Durlevich, O. V. (Одеські астрономічні публікації, 2017)
The General Catalogue of Variable Stars (GCVS) is a large-scale project undertaken in Moscow since 1946 on behalf of the IAU. After a brief outline of its history, we discuss current problems of variable star catalogues and present our plans for the nearest future, including determination of accurate coordinates for all GCVS stars, new Name-lists, improvements of the classification scheme, etc.